Gellan gum as a versatile biopolymer: A 20-year bibliometric review with emerging insights into probiotic delivery - Zaleha Mahmod; Muhammad Faiz Zulkifli; Wan Iryani Wan Ismail; Mohd Ariff Sharifudin; Mohd Hafiz Bin Arzmi; Khairul Anuar Mat Amin (Bioactive Carbohydrates and Dietary Fibre, 2026)

Core genome analysis reveals novel drug and vaccine targets in multidrug-resistant Citrobacter koseri - Zubda Ashraf; Fizza Arshad; Samina N. Shakeel; Faiz Ur Rahman; Khaled Fahmi Fawy; Sarah A. Altwaim; Saeed M. Alasmari; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2026)

Protective effects of Coagulansin-A against LPS-induced inflammatory and oxidative stress responses in human lung epithelial cells - Sadaf Naz; Umakant Yadav; Sidra Faiz; Muhammad Usama Mazhar; Syeda Rida Zainab; Rizwan Ul Haq; Fadi Khasawneh; Ihsan Ul Haq; Muhammad Khalid Tipu; Lin Zhu (Toxicon, 2026)

Mitigation of aflatoxin B1-induced toxicopathology and immunosuppression in broilers using a multimodal antioxidant formulation - Muhammad Asad Ali; Muhammad Abdullah Arshad; Aisha Khatoon; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Muhammad Umar Ijaz; Sadaf Faiz; Aneela Amin (Mycotoxin Research, 2026)

The synergistic role of non-antibiotic agrochemicals and environmental pollutants in driving antimicrobial resistance in poultry systems - Ambreen Leghari; Faiz Muhammad Khand; Shakeel Ahmed Lakho (Journal of Environmental Chemical Engineering, 2026)

Mapping Flood Co-Adaptation Strategies in a Vulnerable River Basin: Engaging Youth in Collaborative Decision-Making - Zulfaqar Sa’adi; Zainura Zainon Noor; Nur Syamimi Zaidi; Ee Ling Yong; Fateha Abdul Razak; Nurul Hana Mohamed; Zainab Mat Lazim; Ainul Syarmimi Rosli; Mohd Faiz Foze; Siti Hanna Elias; Khairunnisa Abdul Halim; Muhammad Burhanuddin Bahrodin; et al. (Environmental Management, 2026)

Natural Concurrent Infection by Water Moulds of the Genera Achlya and Protoachlya in a Red Tilapia ( Oreochromis sp.) Hatchery in Malaysia - Mohammad Amirul Faiz Zulkiply; Muhammad Salahudin Kheirel Anuar; Mohd Termizi Yusof; Annas Salleh; Ina Salwany Md Yasin; Channarong Rodkhum; Mohammad Noor Amal Azmai (Journal of Fish Diseases, 2026)
This paper reports a natural concurrent infection by water moulds of the genera Achlya and Protoachlya in a red tilapia hatchery in Malaysia. In December 2024, a mass mortality of cultured juvenile red tilapia was noticed at 7 days after transportation and introduction into a hatchery. The affected fish showed lethargy at the bottom of the tanks, loss of appetite, pale colouration, and were isolated from the schooling group. Further examination found brownish cotton wool‐like growth, particularly at the operculum, gills, and at the base of the fins. Several fish exhibited clinical signs including fin rot, gill inflammation, and cloudy eyes. Histopathological examination of the gills revealed secondary lamella necrosis, fusion, hyperplasia, and infiltration of leucocytes. Morphological and molecular identifications revealed the presence of Achlya bisexualis , A. prolifera , and Protoachlya paradoxa in the diseased fish. These organisms belong to the Oomycetes, a group of fungus‐like protists rather than true fungi. Achlya bisexualis and A. prolifera were more sensitive to salinity, with a minimum inhibitory concentration of 15 ppt, compared to P. paradoxa , which was more halotolerant until 25 ppt. The isolated oomycetes demonstrated the ability to grow at temperatures ranging from 5°C to 30°C, with growth rates increasing with temperature. A cumulative mortality rate of 68% with estimated losses of RM 1000 was recorded from the outbreak, while gradual increases in water salinity up to 20 ppt helped to reduce the mortality. Saprolegniasis poses a significant threat to tilapia's egg and fingerling productions in hatchery operations. However, a synergistic multispecies infection of the pathogens may exacerbate the problem.

Genomic instability in canine mammary tumors: A comparative focus on loss of heterozygosity and microsatellite alterations with human breast cancer - Faiz Muhammad Khand; Barkat Ali Jatoi; Shakeel Ahmed Lakho; Ambreen Leghari (Mutation Research - Reviews in Mutation Research, 2026)

Vinca Extract Infused Silk Fibroin Hydrogel for Treatment of Artificially Induced Diabetic Foot Ulcer in Murine Model - Ayesha Afzal; Hafiz Muhammad Tahir; Aamir Ali; Ayesha Muzamil; Navera Afzal; Sania Faiz; Farwa Shafeeq; Sidra Arshad; Rida Mahnoor (Cell Biochemistry and Biophysics, 2026)

Climate change as a driver of bovine mastitis: Impacts on environmental pathogen ecology, host susceptibility, and future mitigation strategies - Ambreen Leghari; Faiz Muhammad Khand; Sheereen Laghari; Shakeel Ahmed Lakho (The Veterinary Journal, 2026)

Impact of Various Global Digital Elevation and Crustal Density Models on Accurate Topographic Correction for Geoid Modelling Over East Malaysia - Noorhurul Ain Othman; Muhammad Faiz Pa’suya; Ami Hassan Md Din; Ramazan Alpay Abbak; Mohamad Azril Che Aziz; Chivatsi Jonathan Nyoka; Nurul Shafiqah Hazelin Noor Azmin; Afreena Nisha Mohd Zamri (Pure and Applied Geophysics, 2026)

Mesenchymal stem cell-based therapeutic strategies for female infertility: current evidence and emerging targeting approaches - Muhammad Sajid; Faiz-ul Hassan; Atique Ahmed Behan; Fethi Ahmet Ozdemir; Faisal Siddique; Sarfraz Ali Fazlani; Muhammad Asif Arain; Muhammad Saif-ur Rehman (Biotechnology Letters, 2026)

A hybrid MDBN-CA framework for simulating urban growth and optimizing multidimensional zoning in sustainable urban planning - Esha Malik; Muhammad Nadeem; Jizong Jiao; Mohammad Arsalan Khan; Abdullah Faiz Al Asmari (Environment, Development and Sustainability, 2026)

A review of indoor air quality (IAQ) in classrooms: The effect of particulate matter (PM), gaseous pollutants, and airborne pathogens - Nurul Shahadah Roslan; Mohamad Nur Hidayat Mat; Muhammad Faiz Hilmi Rani (Environmental Pollution, 2026)

Heavy metal contamination in agricultural soils: an environmental and food safety perspective - Siraj ud Din; Muhammad Subhanullah; Bakht Rawan; Shahla Nazneen; Muhammad Ilyas; Thiago Machado da Silva Acioly; Waheed Ullah; Abdullah Faiz Al Asmari; Saiful Islam (Environmental Monitoring and Assessment, 2026)

Eucalyptus wood waste biochar as an eco-friendly adsorbent for arsenic detoxification in wastewater - Yu Shuang Ren; Muhammad Ilyas; Islamud Din; Syeda Maria Ali; Shahid Iqbal; Thiago Machado da Silva Acioly; Zhanate Idrisheva; Khalid Z. Elwakeel; Alibek Ydyrys; Abdullah Faiz Al Asmari; Saiful Islam (Natural Product Research, 2026)

Trends in emerging analytical strategies for okadaic acid detection in aquatic food commodities - Muhammad Saleem; Md Mehedi Hassan; Waqas Ahmad; Liang Tian; Muhammad Fahad Khan; Faiz-ul-Hassan Shah; Yi Xu; Quansheng Chen (Trends in Food Science & Technology, 2026)

Impacts of climate change and local stressors on the coral community structure off the eastern coast of Pakistan - Amjad Ali; Azka Rafiq Malik; Naveed Ahmad; Gulab Said; Zulfiqar Ali Mirani; Seema Shafique; Habibul Hassan; Ateeque Rahman Khooharo; Faiz Muhammad (Regional Studies in Marine Science, 2026)

Multi-omics studies provide insights into selenium-mediated arsenic detoxification and stress tolerance in rice - A review - Muhammad Zahir Ahsan; Faiz Hussain Panhwar; Sadam Hussain Bhutto; Xiaomei Jia; Xiaoying Ye; Zhu Jianqing (Food Bioscience, 2026)

Global composite drought indices for investigating the effects of climate-driven drought on major crop water requirements - Muhammad Abrar Faiz; Liangliang Zhang; Dong Liu; Yongqiang Zhang; Mo Li; Farah Naz (Science China Earth Sciences, 2026)

Selenium-rich rice genotypes mitigate arsenic uptake and accumulation while maintaining agronomic performance in arsenic-contaminated soil - Muhammad Zahir Ahsan; Faiz Hussain Panhwar; Xiaomei Jia; Xiaoying Ye; Chen Rongjun; Li Lihua; Jianqing Zhu (Plant and Soil, 2026)

Correction: Assessment of spatial and seasonal variation in soil heavy metal contamination adjacent to Chini Lake, Malaysia - Mir Sujaul Islam; Faiz Ul Hassan; Mohd Ekhwan Toriman; Raheel Ahmad; Muhammad Amjad Bashir; Abdur Rehim; Qurat‑Ul‑Ain Raza (Environmental Geochemistry and Health, 2026)

Postbiotics and Parabiotics: A Viable Health Promoting Alternative for Poultry Industry—A Comprehensive Review - Zhengtian Li; Sikandar Ali; Muhammad Asif Arain; Faiz-ul Hassan; Fazul Nabi; Muhammad Uzair Akhtar; Hemei Yuan (Probiotics and Antimicrobial Proteins, 2026)

Continuous-Flow Electrocoagulation for Hexavalent Chromium Reduction in Nickel Mining Wastewater: Insights into Optimization and Mechanisms - Muhammad Risal Rusman; Muhammad Sonny Abfertiawan; Faiz Hasan; Mindriany Syafila; Marisa Handajani (Mine Water and the Environment, 2026)
Indonesia’s extensive laterite nickel reserves drive substantial nickel mining activities yet pose environmental risks due to the wastewater’s hexavalent chromium (Cr(VI)) contamination. This study evaluates a continuous-flow electrocoagulation reactor, using aluminum and iron electrodes to remove Cr(VI) from nickel mining wastewater. Optimization via a Box-Behnken design examined current intensity, flow rate, and reactor flow distance. Results revealed that iron electrodes achieved superior Cr(VI) removal efficiency of up to 99% at a flow rate of 0.99 L/min, current intensity of 2 A, and reactor flow distance of 165,6 cm, whereas aluminum electrodes attained a maximum removal efficiency of 83% under optimal conditions of 2.9 A, 0.93 L/min, and 338 cm. Iron electrodes also demonstrated lower specific electrical energy consumption (0.48 kWh/g Cr(VI)) than aluminum (1.39 kWh/g Cr(VI)). Kinetic studies indicated that Cr(VI) removal on aluminum electrodes aligns with a pseudo-first-order model, while iron electrodes follow a second-order model, highlighting a shift from physical to chemical adsorption mechanisms. Adsorption isotherms further supported these findings, with Freundlich isotherms fitting the aluminum electrodes (R 2 = 0.998), suggesting heterogeneous, multilayer adsorption, and Langmuir isotherms fitting the iron electrodes (R 2 = 0.988), indicating homogeneous, monolayer adsorption. This study underscores electrocoagulation’s potential as an energy-efficient and sustainable solution for Cr(VI) removal in mining wastewater treatment.

Assessment of spatial and seasonal variation in soil heavy metal contamination adjacent to Chini Lake, Malaysia - Mir Sujaul Islam; Faiz Ul Hassan; Mohd Ekhwan Toriman; Raheel Ahmad; Muhammad Amjad Bashir; Abdur Rehim; Qurat-Ul-Ain Raza (Environmental Geochemistry and Health, 2026)

A review on the earth observation techniques for coastal vulnerability index in Malaysia - Shin Yi Chen; Nurul Hazrina Idris; Mohammad Hanif Hamden; Amalina Izzati Abdul Hamid; Muhammad Faiz Pa’suya; Norhadija Darwin (International Journal of Remote Sensing, 2026)

The first complete mitochondrial genome characterization of Lutjanus fulvus (Perciformes: Lutjanidae) and phylogenetic analysis within the Lutjanidae family - Luxiu Gao; Yifan Liu; Faiz Muhammad; Taobo Feng; Mingzhe Han; Chi Zhang; Bingjian Liu (Zoologischer Anzeiger, 2026)

Hybrid Gaussian process regression-based harmony assessment in a water–land–energy–food–carbon-emission coupled system - Chunqing Wang; Liangliang Zhang; Dong Liu; Mo Li; Muhammad Abrar Faiz; Tianxiao Li; Song Cui; Muhammad Imran Khan (Journal of Hydrology, 2026)

Moringa oleifera: a comprehensive review with special emphasis on phytochemistry - Muhammad Nazim; Wajid Raza; Faiz ul Hassan Nasim; Shazia Anjum; Hammad Ullah; Asif Nawaz; Muhammad Ayaz; Maria Daglia (Phytochemistry Reviews, 2026)

Synergies and struggles: Water security and climate action in South Asia’s quest for SDG 6 and SDG 13 - Faisal Baig; Assaad Kassem; Md. Zishan Akhter; Saifudeen Kabeer; Muhammad Abrar Faiz; Mirza Farrukh Baig; Mohsen Sherif (Gondwana Research, 2025)

Spatial assessment and ecological risk evaluation of soil heavy metal contamination using multivariate statistical techniques - Mir Sujaul Islam; Faiz Ul Hassan; Mohd Ekhwan Toriman; Raheel Ahmad; Muhammad Amjad Bashir; Abdur Rehim; Qurat-Ul-Ain Raza; Goh Choo Ta; Sharina Binti Abdul Halim (CATENA, 2025)

Insulin Quantification Through Electrochemical and Optical Aptasensors: A Review - Jia Qi Chong; Muhammad Faiz Md Shakhih; Bhuwaneswaran Vijayam; Citartan Marimuthu; Congo Tak Shing Ching; Asnida Abdul Wahab (Annals of Biomedical Engineering, 2025)

Nutritional Intervention with Selenium-Rich Rice Mitigates Arsenic-Induced Liver and Kidney Toxicity in Mice - Muhammad Zahir Ahsan; Faiz Hussain Panhwar; Xiaomei Jia; Xiaoying Ye; Rongjun Chen; Lihua Li; Arab Khan Lund; Jianqing Zhu (Biological Trace Element Research, 2025)

Spectrophotometric Determination of Fluometuron Via Complexation with Fe(III): Method Development, Validation, and Application to Environmental Samples - Mian Muhammad; Mushtaq Ahmad; Sikandar Khan; Faiz Ali (Journal of Fluorescence, 2025)

Heat stress in riverine buffaloes: regulatory mechanism, physiological changes, production and reproductive performance, and mitigation strategies - Faiz-ul Hassan; Nouman Ashraf; Muhammad Asif Arain; Muhammad Mushahid; Muhammad Safdar; Muhammad Saif-ur-Rehman; Atique Ahmed Behan (International Journal of Biometeorology, 2025)

Arsenic speciation using HPLC–ICP–MS in white and brown rice and health risk assessment - Raneesha Navaretnam; Ahmad Zaharin Aris; Muhammad Faizan A. Shukor; Mohd Nor Faiz Norrrahim; Victor Feizal Knight; Teen Teen Chin; Noorain Mohd Isa; Ley Juen Looi (Environmental Geochemistry and Health, 2025)

Field-based evaluation of sugarcane bagasse biochar for managing root-knot nematodes in tomato - Maria Fayyaz; Amjad Abbas; Usman Arshad; Farrukh Azeem; Faiz Ahmad Joyia; Abdelaziz Hajjaji; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2025)

Integration of machine learning and time series analysis for upwelling prediction dashboard in lake Laut tawar, indonesia: A study based on climate forecasting - Muhammad Zia Ulhaq; Muhammad Farid; Zahra Ifma Aziza; Teuku Muhammad Faiz Nuzullah; Fakhrus Syakir; Novi Reandy Sasmita (Theoretical and Applied Climatology, 2025)

Aftershock sequence of the Yogyakarta earthquake 2006 (Mw ~ 6.4), Indonesia, based on analysis of hypocenter relocation, static, and dynamic stress - Mohamad Ramdhan; Kadek Hendrawan Palgunadi; Muhammad Maruf Mukti; Virga Librian; Gatut Daniarsyad; Faiz Muttaqy; Edi Hidayat; Syuhada Syuhada; Muhammad Hanif; Adityo Mursitantyo; Birger-Gottfried Lühr; Andri Dian Nugraha; et al. (Natural Hazards, 2025)

Correction to: Control and effect of climate change due to human activities by mathematical modeling approach under fractional operator - Aqeel Ahmad; Khurram Faiz; Muhammad Farman; Sadia Sattar; Aceng Sambas (Modeling Earth Systems and Environment, 2025)

Control and effect of climate change due to human activities by mathematical modeling approach under fractional operator - Aqeel Ahmad; Khurram Faiz; Muhammad Farman; Sadia Sattar; Aceng Sambas (Modeling Earth Systems and Environment, 2025)

Resistance of ten Indonesian cassava cultivars to the cassava lacebug, Vatiga illudens (Drake) (Hemiptera: Tingidae), a newly invasive exotic species in Asia - Retno Dyah Puspitarini; Ave Maria Simbolon; Chairunisah Putri; Hendy Dwi Bayu Ardianto; Vriescha Ermalitha Ramadhanti Rudiantoyo; Windi Puspa Saputri; Faiz Nashiruddin Muhammad; Ito Fernando (Crop Protection, 2025)

Disaster risk assessment in Malaysia: current state, challenges, and future directions - Muhammad Wafiy Adli Ramli; Nor Eliza Alias; Zulfaqar Sa’adi; Yusrin Faiz Abdul Wahab; Azimah ABD Rahman (Natural Hazards, 2025)

Parity and breastfeeding are contributing factors for geographical differences in breast cancer risk - Boon Hong Ang; Shivaani Mariapun; Farahida Mohd Farid; Imelda Suhanti Ishak; Muhammad Faiz Md Taib; Asfarina Ab Rahim; Lenjai Anak Jembai; Tania Islam; Kartini Rahmat; Farhana Fadzli; Nur Aishah Mohd Taib; Cheng Har Yip; et al. (Cancer Causes & Control, 2025)

Spatial variation of crustal anisotropy in Simeulue Island, Indonesia, from shear wave splitting analysis - Syuhada Syuhada; Faiz Muttaqy; Titi Anggono; Bayu Pranata; Nanang T. Puspito; Mohamad Ramdhan; Febty Febriani; Muhammad Ma'ruf Mukti; Cinantya Nirmala Dewi; Mohammad Hasib; Aditya Dwi Prasetio; Atin Nur Aulia; et al. (Physics of the Earth and Planetary Interiors, 2025)

From bias to accuracy: Transforming satellite precipitation data in arid regions with machine learning and topographical insights - Faisal Baig; Luqman Ali; Muhammad Abrar Faiz; Haonan Chen; Mohsen Sherif (Journal of Hydrology, 2025)

Assessing the Role of Biostimulants in Affecting the Production of Radish and Eggplant - Muhammad Amjad Bashir; Qurat-Ul-Ain Raza; Abdur Rehim; Hafiz Muhammad Ali Raza; Asad Ismail Noor; Mir Sujaul Islam; Faiz-Ul-Hassan; Muhammad Zafar-Ul-Hye; Yucong Geng (Journal of Soil Science and Plant Nutrition, 2025)

Physicochemical, Enzymatic, and Microbial Responses to Phosphofructokinase Overexpressing Transgenic Potato Cultivation: A Pot Experiment - Muhammad Junaid Sadiq Gill; Umer Ali; Aqib Hassan Ali Khan; Ismat Nawaz; Tayyab Ashfaq Butt; Cyrus Raza Mirza; Ameena Iqbal; Arfan Ali; Faiz Ur Rahman; Sohail Yousaf; Mazhar Iqbal (American Journal of Potato Research, 2025)

Revisiting the composite drought index for improving drought monitoring - Muhammad Abrar Faiz; Liangliang Zhang; Dong Liu; Ning Ma; Mo Li; Zhaoqiang Zhou; Faisal Baig; Tianxiao Li; Song Cui (Journal of Hydrology, 2025)

Transcriptomic analyses reveal the upregulation of the fatty acids metabolism genes in Thalassiosira weissflogii during low optimal phosphate concentration - Muhammad Faiz Zakaria; Ahmad Hanafi Ahmad Kamal; Nor Afiqah-Aleng; Mohd Effendy Abd Wahid; Ghows Azzam; Tomoyo Katayama; Kazutaka Takahashi; Kamariah Bakar; Hock Seng Tan; Malinna Jusoh (Aquaculture, 2025)

Attributing rainfall and drought variability across climate vulnerable area of Pakistan: Perspective from different satellite and ground-based datasets - Mohammad Ilyas Abro; Ehsan Elahi; Murad Ali Khaskheli; Rashid Mustafa Korai; Mahdi Hassan; Asghar Ali Majidano; Bhai Khan Solangi; Faiz Muhammad Khokhar (Theoretical and Applied Climatology, 2025)

De novo transcriptome analysis and gene expression profiling of Conticribra weissflogii during low salinity reveals regulation of fatty acid biosynthesis genes - Muhammad Faiz Zakaria; Ahmad Hanafi Ahmad Kamal; Noor Amanina Awang; Nor Afiqah-Aleng; Kamariah Bakar; Noorul Darlina Edlin Abd Rahim; Hock-Seng Tan; Mohd Effendy Abd Wahid; Ghows Azzam; Malinna Jusoh (Journal of Applied Phycology, 2025)

Geochemical evolution, geostatistical mapping and machine learning predictive modeling of groundwater fluoride: a case study of western Balochistan, Quetta - Taimoor Shah Durrani; Malik Muhammad Akhtar; Kaleem U. Kakar; Muhammad Najam Khan; Faiz Muhammad; Maqbool khan; H. Habibullah; Changaiz Khan (Environmental Geochemistry and Health, 2025)

Regulation of energy metabolism by non-coding RNAs in livestock species: a review - Faiz-ul Hassan; Muhammad Safdar; Muhammad Younus; Muhammad Asif Arain (Journal of Comparative Physiology B, 2025)

Removal of pharmaceutical compounds from sewage effluent by the nanofiltration membrane - Zarimah Mohd Hanafiah; Wan Hanna Melini Wan Mohtar; Rosiah Rohani; Muhammad Faiz Fadzizi; Wan Abd Al-Qadr Imad Wan-Mohtar; Khalid Sayed; Teh Sabariah Binti Abdul Manan; Antonius Indarto (Journal of Water Process Engineering, 2024)

The protective effect and mechanism of selenium-rich rice-based selenoproteins and sodium selenite against D-galactose-induced aging mice - Ling Li; Meilin Li; Muhammad Zahir Ahsan; Faiz Hussain Panhwar; Zhang Yue; Dan Luo; Yang Su; Xiaomei Jia; Xiaoying Ye; Chen Rongjun; Li Lihua; Jianqing Zhu (Food Bioscience, 2024)

The optimization of marine geoid model from altimetry data using Least Squares Stokes modification approach with additive corrections across Malaysia - Nornajihah Mohammad Yazid; Ami Hassan Md Din; Muhammad Faiz Pa’suya; Abdullah Hisam Omar; Nazirah Mohamad Abdullah; Mohammad Hanif Hamden (International Journal of Remote Sensing, 2024)

Integration of Local Mean Sea Level and Land Vertical Datum over Peninsular Malaysia via Transformation Model - Muhammad Faiz Pa’suya; Ami Hassan Md Din; Ramazan Alpay Abbak; Noorfatekah Talib; Mohamad Azril Che Aziz; Muhammad Zahir Ramli; Mohammad Hanif Hamden; Nornajihah Mohammad Yazid (Pure and Applied Geophysics, 2024)

Correction: Cold atmospheric plasma-activated medium for potential ovarian cancer therapy - Shazia Tabassum; Muhammad Noman Khan; Nosheen Faiz; Almas; Bushra Yaseen; Iftikhar Ahmad (Molecular Biology Reports, 2024)

Cold atmospheric plasma-activated medium for potential ovarian cancer therapy - Shazia Tabassum; Muhammad Noman Khan; Nosheen Faiz; Almas; Bushra Yaseen; Iftikhar Ahmad (Molecular Biology Reports, 2024)

Structural and in vitro starch digestion of wheat flour noodles by calcium mediated gelation of low methoxyl pectin - Muhammad Faiz Bin Muhd Faizal Abdullah Tan; Oni Yuliarti; Adeline Ik Chian Wong; Jerome Jie Long Wong (Food Structure, 2024)

Nuclear integration of MYB36 and APX-1 genes impart heat tolerance in wheat - Hina Firdous; Arfan Ali; Muhammad Mubashar Zafar; Faiz Ahmad Joyia; Muhammad Hamza; Abdul Razzaq; Muhammad Uzair; Sezai Ercisli; Waqas Shafqat Chattha; Mahmoud F. Seleiman; Naeem Khan; Xuefei Jiang (Functional & Integrative Genomics, 2024)

Batch Electrocoagulation Process for the Removal of High Colloidal Clay from Open-Cast Coal Mine Water Using Al and Fe Electrodes - Muhammad Sonny Abfertiawan; Mindriany Syafila; Marisa Handajani; Faiz Hasan; Hanifah Oktaviani; Firman Gunawan; dan Febriwiadi Djali (Mine Water and the Environment, 2024)
Open-cast coal mining operations can produce water with high amounts of total suspended solids (TSS). We tested the use of electrocoagulation for the removal of colloidal clay from mine water. Monopolar batch electrocoagulation was performed at the laboratory scale using Al and Fe electrodes and varying the DC current (0.5, 1, and 2 A) and contact time (15, 30, and 45 min). Aluminum electrode electrocoagulation with a current of 2 A and a contact time of 15 min had the greatest TSS removal efficiency (99%), with concentrations decreasing from 5,400 to 23 mg/L. The greatest removal (98 and 99%, respectively) was obtained using an Al electrode with an electric current of 0.5 and 1 A, with 30 min of contact time. With an Fe electrode, the greatest efficiency was achieved with a current of 2 A and a contact time of 30 min. The TSS removal efficiency reached 98% while the concentration dropped to 66 mg/L, followed by 89% and 95% for the 0.5 A-45 min and 1 A-15 min variations, respectively.

In vivo evaluation of efficacy and safety of Coagulansin-A in treating arthritis - Sadaf Naz; Muhammad Usama Mazhar; Sidra Faiz; Maria Nawaz Malik; Jehan Zeb Khan; Ihsan Ul Haq; Lin Zhu; Muhammad Khalid Tipu (Toxicology and Applied Pharmacology, 2024)

Estimation of the zero-height geopotential value and datum offset for the Kenya vertical network using an optimized earth model - Chivatsi Jonathan Nyoka; Ami Hassan Md Din; Muhammad Faiz Pa'suya (Journal of African Earth Sciences, 2024)

Development and validation of an indirect ELISA for the serodiagnosis of contagious caprine pleuropneumonia in goats - Hayatullah Khan; Farhan Anwar Khan; Umer Sadique; Ijaz Ahmad; Muhammad Saeed; Faisal Ahmad; Faiz Ur Rehman; Hanif Ur Rahman (Small Ruminant Research, 2024)

Detailed seismic structure beneath the earthquake zone of Yogyakarta 2006 (Mw ∼6.4), Indonesia, from local earthquake tomography - Virga Librian; Mohamad Ramdhan; Andri Dian Nugraha; Muhammad Maruf Mukti; Syuhada Syuhada; Birger-Gottfried Lühr; Sri Widiyantoro; Adityo Mursitantyo; Ade Anggraini; Zulfakriza Zulfakriza; Faiz Muttaqy; Yayan Mi'rojul Husni (Physics of the Earth and Planetary Interiors, 2024)

Evaluation of drought hazards and coping strategies adopted by pastoral communities in the Cholistan Rangeland of Pakistan - Muhammad Farooq Azhar; Muhammad Junaid Faiz; Ehsan Ali; Abida Aziz; Muhammad Akbar; Ghulam Raza; Muhammad Abdullah; Muhammad Muzammil Habib; Muhammad Farooq Akram (Environmental Development, 2024)

Comparative genomic studies on the TGF-β superfamily in blue whale - Zunaira Faiz; Shakeela Parveen; Saba Saeed; Muhammad Tayyab; Mehwish Sultana; Muhammad Hussain; Zainab Shafqat (Mammalian Genome, 2024)

Measurement and analysis of regional water-energy-food nexus resilience with an improved hybrid kernel extreme learning machine model based on a dung beetle optimization algorithm - Zhiqin Zhang; Liangliang Zhang; Dong Liu; Nan Sun; Mo Li; Muhammad Abrar Faiz; Tianxiao Li; Song Cui; Muhammad Imran Khan (Agricultural Systems, 2024)

How accurate are the machine learning models in improving monthly rainfall prediction in hyper arid environment? - Faisal Baig; Luqman Ali; Muhammad Abrar Faiz; Haonan Chen; Mohsen Sherif (Journal of Hydrology, 2024)

Energy and social factor decomposition to identify drivers impeding sustainable environmental transition in emerging countries: SDGs-2030 progress assessment using LMDI analysis - Qi Gao; Nida Raza; Dandan Sun; Muhammad Akmal; Faiz Nayab (Environmental Science and Pollution Research, 2024)

Retention of methyl iodide on metal and TEDA impregnated activated carbon using indigenously developed setup - Talhat Yaqoob; Masroor Ahmad; Yasir Faiz; Farman Ali; Amjad Farooq; Faisal Faiz; Attaullah Shah; Muhammad Asim Irshad; Naseem Irfan; Nisar Ali; Sahid Mehmood (Environmental Research, 2023)

Engineering of insecticidal hybrid gene into potato chloroplast genome exhibits promising control of Colorado potato beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) - Md. Jakir Hossain; Allah Bakhsh; Faiz Ahmad Joyia; Emre Aksoy; Neslihan Zahide Özturk Gökçe; Muhammad Sarwar Khan (Transgenic Research, 2023)

Groundwater vulnerability to contamination in the gulf cooperation council region: A review - Faisal Baig; Mohsen Sherif; Ahmed Sefelnasr; Muhammad Abrar Faiz (Groundwater for Sustainable Development, 2023)

Spatial variability and hydrochemical quality of groundwater of Hyderabad Rural, Sindh, Pakistan - Laeeq Ahmed Khan Khokhar; Muhammad Yar Khuhawar; Taj Muhammad Jahangir Khuhawar; Muhammad Farooque Lanjwani; Ghulam Murtaza Arain; Faiz Muhammad Khokhar; Mezhar Iqbal Khaskheli (Sustainable Water Resources Management, 2023)

Synoptic conditions triggering extreme flood events in Bintan Island in early January 2021 - Ida Narulita; Faiz R. Fajary; Muhammad Rais Abdillah; M. R. Djuwansah; Dwita Sutjiningsih; Eko Kusratmoko; Setyo S. Moersidik (Meteorology and Atmospheric Physics, 2023)

Structural properties of meat analogue with added konjac gels - Oni Yuliarti; Lisa Ng; Wen Min Koh; Muhammad Faiz Bin Muhd Faizal Abdullah Tan; Aan Dwi Sentana (Food Hydrocolloids, 2023)

Diurnal variation in the atmospheric electric field with respect to aerosol and meteorological parameters at Islamabad, Pakistan - Samia Faiz Gurmani; Nabeel Ahmad; Tabinda Shamsher; Tariq Mehmood; Waqas Khalid; Asghari Maqsood; Talat Iqbal; Muhammad Ali Shah (Journal of Earth System Science, 2023)

Bibliometric approach to trehalulose research trends for its potential health benefits - Muhammad Faiz Zulkifli; Mohanasundarapandian Sivakumar; M. Maulidiani; Wan Iryani Wan Ismail (Food Bioscience, 2023)

Current Status of Coral Reef Fish Abundances at Pulau Bidong and Nearby Islands, South China Sea Using Stereo-Diver Operated Video System - Aminudin Muhammad Afiq-Firdaus; Che Din Mohd Safuan; Suhaidi Shafie; Lila Iznita Izhar; Ezmahamrul Afreen Awalludin; Muhammad Faiz Ahmad; Nur Arbaeen Mohd Johari; Zainudin Bachok (Ocean Science Journal, 2023)

Time series analysis for droughts characteristics response to propagation - Muhammad Abrar Faiz; Yongqiang Zhang; Xiaoqiang Tian; Xuanze Zhang; Ning Ma; Santosh Aryal; Farah Naz (International Journal of Climatology, 2023)
Understanding and exploring hydrological (H) or soil moisture (SM) drought due to meteorological (M) drought under changing climate is crucial for drought early warning. Previously, different methods were used to calculate drought propagation from one state (M to another [H or SM]). However, each method has its pros and cons and thus cannot describe appropriate propagation attributes. In this study, a time series analysis is carried out to explore the propagation process in the Yellow River Basin (YRB) and Hai River Basin (HRB) of China. Standardized Streamflow Index (SSI), Standardized SM Index (SSMI), and Standardized Precipitation Index (SPI) 1‐month time series were calculated using streamflow, satellite‐based SM, and precipitation from 1979 to 2016. The time series framework identifies the average drought propagation as 3.4–8.3 months (M–H) and 2.3–5 months (M–SM) in YRB, while 2.8–7.7 months (M–H) and 2.3–8.5 months (M–SM) in HRB. Cross‐wavelet analysis indicated that periodic characteristics of M drought are responsible for these droughts. Overall, the findings of this study may help to minimize the drought hazards posed by M droughts.

Investigating the nexus between critical success factors, supportive leadership, and entrepreneurial success: evidence from the renewable energy projects - Muttahir Hussain; Samma Faiz Rasool; Wang Xuetong; Muhammad Zaheer Asghar; Abdulmohsen Saleh A. Alalshiekh (Environmental Science and Pollution Research, 2023)

Understanding the role of catchment and climate characteristics in the propagation of meteorological to hydrological drought - Hadush Meresa; Yongqiang Zhang; Jing Tian; Muhammad Abrar Faiz (Journal of Hydrology, 2023)

Prosperity risk assessment by heavy metal contamination on human health and multivariate statistical analysis of groundwater as a drinking source - Laeeq Ahmed Khan Khokhar; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Ghulam Murtaza Arain; Faiz Muhammad Khokhar; Mazhar Iqbal Khaskheli; Shaishta Khan; Muhammad FarooqueLajwani; Muhammad Ilyas Abro; Zahid Ali Zounr (Arabian Journal of Geosciences, 2023)

Health impacts from TRAPs and carbon emissions in the projected electric vehicle growth and energy generation mix scenarios in Malaysia - Soo Chen Kwan; Sazalina binti Zakaria; Mohd Faiz Ibrahim; Wan Rozita Wan Mahiyuddin; Nurzawani Md Sofwan; Muhammad Ikram A Wahab; Radin Diana R. Ahmad; Ahmad Rosly Abbas; Wei Kian Woon; Mazrura Sahani (Environmental Research, 2023)

Public understanding of rip current and beach safety at Teluk Cempedak Recreational Beach in Pahang, Malaysia - Muhammad Zubir Yusof; Muhammad Zahir Ramli; Siti Fairuz Che Othman; Yusairah Amani Mohd Aliziyad; Juliana Mohamed; Muhammad Faiz Pa’suya; Abdul Nasir Abdul Ghafar; Waheb A. Jabbar (Natural Hazards, 2023)

Prevalence of FANCM germline variants in BRCA1/2 negative breast and/or ovarian cancer patients from Pakistan - Muhammad Usman Rashid; Noor Muhammad; Umara Shehzad; Faiz Ali Khan; Asif Loya; Ute Hamann (Familial Cancer, 2023)

Hybrid geoid model over peninsular Malaysia (PMHG2020) using two approaches - Muhammad Faiz Pa’suya; Ami Hassan Md Din; Ramazan Alpay Abbak; Mohammad Hanif Hamden; Nornajihah Mohammad Yazid; Mohamad Azril Che Aziz; Mohd Adhar Abd Samad (Studia Geophysica et Geodaetica, 2022)

Nutritional compositions, pathogenic microorganisms and heavy metal concentration in green turtle eggs (Chelonia mydas) from Terengganu and Sabah, Malaysia - Nor Hashikin Katni; Amirul Faiz Mohd Azmi; Maizah Mohd Abdullah; Mohd Uzair Rusli; Zunita Zakaria; Tengku Rinalfi Putra Tengku Azizan; Azlan Che’ Amat; Mohd Zamri Saad; Ina Salwany Md. Yasin; Muhammad Farhan Nazarudin; Hasliza Abu Hassim (Frontiers in Marine Science, 2022)
A total of 60 green turtle eggs were obtained from sampling sites in Terengganu and Sabah, Malaysia. Isolation and identification of bacteria from these eggs resulted in 12 genera of Gram-negative bacteria with 12 different species. The most frequently isolated bacteria were Salmonella (30.9%) and Proteus (23.7%). The rest of the microorganisms were Aeromonas, Escherichia, Citrobacter, Enterobacter, Klebsiella, Morganella, Pseudomonas, Shigella, Serratia and Photobacterium. A slight difference in total crude protein content was recorded in the samples from Terengganu and Sabah, at 16.3% Dry matter (DM) and 15.8% DM, respectively. Meanwhile, the crude fat content found in the samples from Terengganu was 9.88% DM and 7.79% DM from Sabah. In this study, α-linolenic acid, C18:3 n-3 (Terengganu: 16.87% DM) and linoleic acid, C18:2 n-6 (Sabah: 15.19% DM) were the most prevalent fatty acids in both samples. The green turtle egg samples from Terengganu showed higher value of total saturated fatty acid, total C18:3 n-3 and C18:2 n-6 and total polyunsaturated fatty acids as compared to green turtle eggs from Sabah. The results also revealed that majority of the essential amino acids (EAA) recorded in samples from both sampling sites was lysine (9.67% DM), with higher value recorded in green turtle egg from Terengganu. However, there were no significant differences ( p >0.05) in the nutritional compositions, fatty acid contents and amino acid compositions of the samples between the two sampling sites. Meanwhile, statistical analysis showed significant differences in heavy metal concentrations between the two sampling sites for all the six heavy metals detected in this study (Hg, Cd, Pb, Mn, Zn and Cu). The ranking of heavy metals concentration in turtle eggs from both sampling sites, in decreasing order is as follows: Zn > Cu > Mn > Pb > Cd > Hg. Overall, these results reveal the contents and contaminations of a green turtle egg, which may raise concern on public health risks. Findings from this study will also be beneficial for the future conservation of green turtle population when the consumption of their eggs should be stopped.

Improving the Accuracy of Local Gravimetric Geoid Modelling Using Simulated Terrestrial Gravity Data - Shazad Jamal Jalal; Tajul Ariffin Musa; Ami Hassan Md Din; Wan Anom Wan Aris; Muhammad Faiz Pa’suya (Pure and Applied Geophysics, 2022)

Temperature-Dependent Speciation Analysis of Chromium Immobilized in Calcium Hydroxyapatite Matrix - Sajid Iqbal; Yasir Faiz; Messaoud Harfouche; Muhammad Saifullah; Jong-Il Yun (International Journal of Environmental Research, 2022)

Investigation of Morchella esculenta and Morchella conica for their antibacterial potential against methicillin-susceptible Staphylococcus aureus, methicillin-resistant Staphylococcus aureus and Streptococcus pyogenes - Faiz Ul Haq; Muhammad Imran; Sidrah Saleem; Usman Aftab; Ayesha Ghazal (Archives of Microbiology, 2022)

Correction to: Fabrication, Evaluation, In Vivo Pharmacokinetic and Toxicological Analysis of pH-Sensitive Eudragit S-100-Coated Hydrogel Beads: a Promising Strategy for Colon Targeting - Sadia Rehman; Nazar Muhammad Ranjha; Hina Shoukat; Asadullah Madni; Faiz Ahmad; M. Rafi Raza; Qazi Adnan Jameel; Abdul Majeed; Nasreen Ramzan (AAPS PharmSciTech, 2022)

A new endophytic fungus CJAN1179 isolated from the Cholistan desert promotes lateral root growth in Arabidopsis and produces IAA through tryptophan-dependent pathway - Adeela Naureen; Faiz-ul H. Nasim; Muhammad S. Choudhary; Muhammad Ashraf; Florian M. W. Grundler; A. Sylvia S. Schleker (Archives of Microbiology, 2022)
Fungi, important for growth of plants in arid lands, are expected to be involved in novel biochemical activities during fungal–plant interactions. We isolated 150 fungi associated with rhizosphere and root endosphere of two perennial grasses, Cymbopogon jwarancusa and Panicum antidotale , from Cholistan desert. The isolates were screened for their impact on plant growth and development using Arabidopsis thaliana (Col-0) as a model system. A root-endophytic fungus CJAN1179 from C. jwarancusa showed the highest plant growth-promoting effects. The most remarkable was enhanced number of lateral roots (3.1-fold). CJAN1179 produced indole-3-acetic acid (IAA) particularly in the presence of tryptophan. ITS sequence and phylogenetic analysis characterisation suggested the fungus to be a new species within Sordariomycetidae. CJAN1179 appears to promote plant growth by secreting IAA using tryptophan as a precursor. This fungus can be further explored for its suitability to promote growth of commercially important crops, particularly in arid regions.

Metabolite profile and gene expression of the roots of oil palm seedlings treated with Hendersonia GanoEF1 and infected with Ganoderma boninense - Muhammad Faiz Ismail; Rosimah Nulit; Idris Abu Seman; Mohd Hafiz Ibrahim; Nurrashyeda Ramli (Journal of Plant Pathology, 2022)

Copper Nanoparticles as Growth Promoter, Antioxidant and Anti-Bacterial Agents in Poultry Nutrition: Prospects and Future Implications - Muhammad Sharif; Muhammad Aziz-ur Rahman; Bilal Ahmed; Rao Zahid Abbas; Faiz-ul Hassan (Biological Trace Element Research, 2021)

Refinement of gravimetric geoid model by incorporating terrestrial, marine, and airborne gravity using KTH method - Muhammad Faiz Pa’suya; Ami Hassan Md Din; Mohd Yunus Mohd Yusoff; Ramazan Alpay Abbak; Mohammad Hanif Hamden (Arabian Journal of Geosciences, 2021)

Comparison of Early Succession and Scleractinian Recruitment Between Artificial Live Rocks and Terracotta Tiles - Yusof Muhammad Hamizan; Shahbudin Saad; Mohd Azrul Naim; Mohd Fikri Akmal Khodzori; Muhammad Faiz Mohd Hanapiah (Ocean Science Journal, 2021)

Air pollution and child health: the impact of brick kiln pollution on children's cognitive abilities and physical health in Pakistan - Muhammad Nasir; Faiz Ur Rehman; Shabana Kishwar; Saima Bashir; Muhammad Adil (Environment, Development and Sustainability, 2021)

Revisiting the Effects of Different Dietary Sources of Selenium on the Health and Performance of Dairy Animals: a Review - Muhammad Adeel Arshad; Hossam Mahrous Ebeid; Faiz-ul Hassan (Biological Trace Element Research, 2021)

Prediction of changes in water balance of Nam Co Lake under projected climate change scenarios - Muhammad Adnan; Shichang Kang; Muhammad Saifullah; Shiyin Liu; Guoshuai Zhang; Qiudong Zhao; Muhammad Abrar Faiz; Muhammad Zaman (Hydrological Sciences Journal, 2021)

Inhibition of jack bean urease by amphiphilic peptides - Zafar Ali Shah; Sadam Hussain; Serab Khan; Nawab Ali; Samiullah Burki; Syed Uzair Ali Shah; Ashfaq Ahmad; Faiz -Ur-Rehman; Muhammad Nasimullah Qureshi; Syed Muhammad Mukrram Shah; Farzana Shaheen (Medicinal Chemistry Research, 2021)

Non-obstructive monitoring of muscle fatigue for low intensity dynamic exercise with infrared thermography technique - Muhammad Faiz Md Shakhih; Nursyazana Ridzuan; Asnida Abdul Wahab; Nurul Farha Zainuddin; Laila Fadhillah Ulta Delestri; Anis Suzziani Rosslan; Mohammed Rafiq Abdul Kadir (Medical & Biological Engineering & Computing, 2021)

Identification and inter‐comparison of appropriate long‐term precipitation datasets using decision tree model and statistical matrix over China - Muhammad Abrar Faiz; Yongqiang Zhang; Faisal Baig; Dariusz Wrzesiński; Farah Naz (International Journal of Climatology, 2021)
The reliability of long‐term precipitation estimates is vital for climatology and hydrometeorology applications. Different climatic zones and high rain gauge network (more than 800) of China are a suitable topography for performance evaluation of different long‐term precipitation datasets. In this study, seven long‐term precipitation datasets are tested against in situ observations at different time scales (1981–2016) at 813 grid points. Well‐known statistical indicators and Fast‐frugal tree (FFt) decision model are employed to identify the best long‐term datasets. Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks Climate Data Record is the only datasets that did not perform well in the study area. Asian Precipitation‐Highly‐Resolved Observational Data Integration Towards Evaluation (APHRODITE), Global Precipitation Climatology Centre (GPCC), and Climate Prediction Center (CPC‐Global) estimates are comparable with in situ observations. Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS), National Centers for Environmental Prediction (NCEP2) overestimate the precipitation extremes in the region. There exists a difference of 100–250 mm among precipitation datasets at an annual scale. All of the seven long‐term datasets underestimate the rxdays across China. The minimum range of rxdays (maximum precipitation amount in under defined days: 1 day or 5 days) captured by datasets is comparable except PERSIANN‐CDR. The maximum range calculated with PERSIANN‐CDR is 55.01 (rx1day), and 129.67 (rx5day), much less than the in situ rxdays. This analysis shows that datasets failed to capture maximum precipitation intensity in the region as well. FFt decision model results show that APHRODITE ranked first based on calculated consecutive dry days among all six other datasets in the most climatic zones. Overall, results indicate that data assimilation, the spatial coverage of ground stations, and interpolation techniques used to develop the datasets may limit the reliability of precipitation datasets in the study area.

Fabrication, Evaluation, In Vivo Pharmacokinetic and Toxicological Analysis of pH-Sensitive Eudragit S-100-Coated Hydrogel Beads: a Promising Strategy for Colon Targeting - Sadia Rehman; Nazar Muhammad Ranjha; Hina Shoukat; Asadullah Madni; Faiz Ahmad; M. Rafi Raza; Qazi Adnan Jameel; Abdul Majeed; Nasreen Ramzan (AAPS PharmSciTech, 2021)

Assessment of the response of climate variability and price anomalies to grain yield and land use in Northeast China - Trinh Thi Viet Ha; Muhammad Abrar Faiz; Li Shuang (Environmental Science and Pollution Research, 2021)

Application of an improved multifractal detrended fluctuation analysis approach for estimation of the complexity of daily precipitation - Liangliang Zhang; Heng Li; Dong Liu; Qiang Fu; Mo Li; Muhammad Abrar Faiz; Shoaib Ali; Muhammad Imran Khan; Tianxiao Li (International Journal of Climatology, 2021)
Affected by climate change and high‐intensity human activities, the precipitation series is characterized by nonlinear complex fluctuations. In order to accurately quantify the precipitation complexity, the complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) method was introduced to address the shortcomings of the traditional multifractal detrended fluctuation analysis (MFDFA), and the CEEMDAN‐MFFA method was proposed to explore the spatiotemporal variability and possible causes of precipitation complexity in Northeast China (NEC). The results showed that the traditional MFDFA method generally overestimated precipitation complexity. However, the CEEMDAN‐MFFA method improved the accuracy and reliability of precipitation complexity analysis. Daily precipitation series in NEC were characterized by multifractal with high uncertainty and anti‐persistence. The lowest precipitation complexity was 0.573, which appeared in Qian'an, Jilin Province, and the highest precipitation complexity was 1.108, which appeared in the Boketu, Inner Mongolia. The cities with high complexity of daily precipitation are sporadically distributed in the three provinces of Heilongjiang, Jilin and Liaoning. The average complexity is ~0.892, accounting for 22.5% of the total administrative districts. The complexity of daily precipitation showed a statistically insignificant downward trend with time. The precipitation dynamics structure in the southeast and northwest of the study area was complex, and the precipitation was less predictable than other regions. However, the precipitation dynamics structure was relatively simple and the precipitation was easily predictable in the northeastern, central and southwestern regions. Elevation, topographic relief, changes in water area, forest area and agricultural production were the main influencing factors for the differences in precipitation complexity. Results also revealed that increasing the area of forestland by means of protecting and breeding forests, via regulation of the forest ecosystems to alleviate the complex precipitation process will become a reliable approach to cope with nonstationary precipitation.

Rescue effects of Se-enriched rice on physiological and biochemical characteristics in cadmium poisoning mice - Yang Su; Ling Li; Muhammad Umer Farooq; Xin Huang; Tengda Zheng; Yu Jie Zhang; Hla Hla Ei; Faiz Hussain Panhwar; Zhichen Tang; Rui Zeng; Yuanke Liang; Xiaoying Ye; et al. (Environmental Science and Pollution Research, 2021)

Development of an integrated weighted drought index and its application for agricultural drought monitoring - Muhammad Ahmad Niaz; Muhammad Abrar Faiz; Wei Yongxia (Arabian Journal of Geosciences, 2021)

Mechanistic Approaches of Internalization, Subcellular Trafficking, and Cytotoxicity of Nanoparticles for Targeting the Small Intestine - Asadullah Madni; Sadia Rehman; Humaira Sultan; Muhammad Muzamil Khan; Faiz Ahmad; M. Rafi Raza; Nadia Rai; Farzana Parveen (AAPS PharmSciTech, 2020)

Genetic Structure of Amphioctopus ovulum (Mollusca: Cephalopoda: Octopodidae) as Revealed by Mitochondrial and Nuclear DNA - Faiz Muhammad; Canfeng Dou; Liqin Liu; Gong Li; Punhal Lashari; Zhen-ming Lü (Thalassas: An International Journal of Marine Sciences, 2020)

Comparative Assessment of Reference Evapotranspiration Estimation Using Conventional Method and Machine Learning Algorithms in Four Climatic Regions - Ali Raza; Muhammad Shoaib; Muhammad Abrar Faiz; Faisal Baig; Mudasser Muneer Khan; Muhammad Kaleem Ullah; Muhammad Zubair (Pure and Applied Geophysics, 2020)

Effects of land use and climate variability on the main stream of the Songhua River Basin, Northeast China - Muhammad Abrar Faiz; Dong Liu; Qiang Fu; Faisal Baig; Ahmad Niaz; Tianxiao Li (Hydrological Sciences Journal, 2020)

Population Genetics of Konosirus punctatus in Chinese Coastal Waters Inferred From Two mtDNA Genes (COI and Cytb) - Bingjian Liu; Kun Zhang; Kehua Zhu; Muhammad Shafi; Li Gong; Lihua Jiang; Liqin Liu; Faiz Muhammad; Zhenming Lü (Frontiers in Marine Science, 2020)

Nano-particles of Trace Minerals in Poultry Nutrition: Potential Applications and Future Prospects - Safdar Hassan; Faiz-ul Hassan; Muhammad Saif-ur Rehman (Biological Trace Element Research, 2020)

Synthesis and characterization of newly synthesized neodymium zirconate zinc sulfide nanocomposite and its effect on selected aspects of albino mice behavior - Tafheem Khosa; Aysha Faiz; Asia Hayder; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Application of non-conventional soft computing approaches for estimation of reference evapotranspiration in various climatic regions - Ali Raza; Muhammad Shoaib; Afzaal Khan; Faisal Baig; Muhammad Abrar Faiz; Mudasser Muneer Khan (Theoretical and Applied Climatology, 2020)

Population diversity of Cistopus indicus inferred from mitochondrial DNA (Cytochrome b) variation from China and Vietnam - Canfeng Dou; Faiz Muhammad; Liqin Liu; Li Gong; Yongjiu Chen; Baoying Guo; Zhenming Lü (Molluscan Research, 2020)

The potential applications of picotechnology in biomedical and environmental sciences - Muhammad Zeeshan Qasim; Hafiz Mohkum Hammad; Farhat Abbas; Shafqat Saeed; Hafiz Faiq Bakhat; Wajid Nasim; Wajid Farhad; Faiz Rabbani; Shah Fahad (Environmental Science and Pollution Research, 2020)

Diversity and Abundance of Scleractinian Corals in the East Coast of Peninsular Malaysia: A Case Study of Redang and Tioman Islands - Khodzori Fikri Akmal; Saad Shahbudin; Mohd Hanapiah Muhammad Faiz; Yusof Muhammad Hamizan (Ocean Science Journal, 2019)

Characterization of recombinant endo-1,4-β-xylanase of Bacillus halodurans C-125 and rational identification of hot spot amino acid residues responsible for enhancing thermostability by an in-silico approach - Malik Siddique Mahmood; Faiz Rasul; Mahjabeen Saleem; Amber Afroz; Muhammad Faheem Malik; Naeem Mehmood Ashraf; Umar Rashid; Shumaila Naz; Nadia Zeeshan (Molecular Biology Reports, 2019)

Genetic structure of Amphioctopus fangsiao (Mollusca, Cephalopoda) in Chinese waters inferred from variation in three mtDNA genes (ATPase 6, ND2, and ND5) - Faiz Muhammad; Wei Chen; Liqin Liu; Li Gong; Xun Du; Muhammad Shafi; Zhen-ming Lü (Hydrobiologia, 2019)

Foliar uptake of arsenic nanoparticles by spinach: an assessment of physiological and human health risk implications - Natasha; Muhammad Shahid; Camille Dumat; Sana Khalid; Faiz Rabbani; Abu Bakr Umer Farooq; Muhammad Amjad; Ghulam Abbas; Nabeel Khan Niazi (Environmental Science and Pollution Research, 2019)

Assessment of precipitation variability and uncertainty of stream flow in the Hindu Kush Himalayan and Karakoram River basins of Pakistan - Muhammad Abrar Faiz; Dong Liu; Qiang Fu; Dariusz Wrzesiński; Shehakk Muneer; Muhammad Imran Khan; Tianxiao Li; Song Cui (Meteorology and Atmospheric Physics, 2019)

Multifractal Detrended Fluctuation Analysis of Regional Precipitation Sequences Based on the CEEMDAN-WPT - Dong Liu; Chen Cheng; Qiang Fu; Chunlei Liu; Mo Li; Muhammad Abrar Faiz; Tianxiao Li; Muhammad Imran Khan; Song Cui (Pure and Applied Geophysics, 2018)

Natural Dietary Supplementation of Anthocyanins via PI3K/Akt/Nrf2/HO-1 Pathways Mitigate Oxidative Stress, Neurodegeneration, and Memory Impairment in a Mouse Model of Alzheimer’s Disease - Tahir Ali; Taehyun Kim; Shafiq Ur Rehman; Muhammad Sohail Khan; Faiz Ul Amin; Mehtab Khan; Muhammad Ikram; Myeong Ok Kim (Molecular Neurobiology, 2018)

Stream flow variability and drought severity in the Songhua River Basin, Northeast China - Muhammad Abrar Faiz; Dong Liu; Qiang Fu; Muhammad Uzair; Muhammad Imran Khan; Faisal Baig; Tianxiao Li; Song Cui (Stochastic Environmental Research and Risk Assessment, 2018)

Projection Pursuit Evaluation Model of Regional Surface Water Environment Based on Improved Chicken Swarm Optimization Algorithm - Dong Liu; Chunlei Liu; Qiang Fu; Tianxiao Li; Muhammad Imran Khan; Song Cui; Muhammad Abrar Faiz (Water Resources Management, 2018)

Complexity measurement of precipitation series in urban areas based on particle swarm optimized multiscale entropy - Dong Liu; Chen Cheng; Qiang Fu; Yongjia Zhang; Yuxiang Hu; Dan Zhao; Muhammad Imran Khan; Muhammad Abrar Faiz (Arabian Journal of Geosciences, 2018)

PAAN135, a novel rhizospheric fungus associated with Cholistan desert grass Panicum antidotale, is a species of Saccharomycetales and a new source of cyclo-L-prolylglycine diketopiperazine - Faiz-ul-Hassan Nasim; Adeela Naureen; Muhammad Saleem; Naheed Riaz; Muhammad Shafiq Choudhary; Muhammad Ashraf (Symbiosis, 2018)

Coral recruitment success and sessile benthic colonisation estimation in Tioman Island Marine Park, Malaysia - M. H. Muhammad Faiz; S. Shahbudin; Yukinori Mukai (Journal of Coastal Conservation, 2017)

Reconsidering betaine as a natural anti-heat stress agent in poultry industry: a review - Muhammad Saeed; Daryoush Babazadeh; Muhammad Naveed; Muhammad Asif Arain; Faiz Ul Hassan; Sun Chao (Tropical Animal Health and Production, 2017)

Projected Changes of Future Extreme Drought Events under Numerous Drought Indices in the Heilongjiang Province of China - Muhammad Imran Khan; Dong Liu; Qiang Fu; Qaisar Saddique; Muhammad Abrar Faiz; Tianxiao Li; Muhammad Uzair Qamar; Song Cui; Chen Cheng (Water Resources Management, 2017)

Rainfall Extremes: a Novel Modeling Approach for Regionalization - Muhammad Uzair Qamar; Muhammad Azmat; Muhammad Adnan Shahid; Daniele Ganora; Shakil Ahmad; Muhammad Jehanzeb Masud Cheema; Muhammad Abrar Faiz; Abid Sarwar; Muhammad Shafeeque; Muhammad Imran Khan (Water Resources Management, 2017)

Recent Climate Trends and Drought Behavioral Assessment Based on Precipitation and Temperature Data Series in the Songhua River Basin of China - Muhammad Imran Khan; Dong Liu; Qiang Fu; Shuhua Dong; Umar Waqas Liaqat; Muhammad Abrar Faiz; Yuxiang Hu; Qaisar Saddique (Water Resources Management, 2016)

Analysis of the Appropriate Development Scale of Regional Paddy Field Under the Restriction of Water Resources - Dong Liu; Dan Zhao; Qiang Fu; Tianxiao Li; Muhammad Imran Khan; Wenting Liu; Faiz M. Abrar (Agricultural Research, 2016)

Precipitation variability assessment of northeast China: Songhua River basin - Muhammad Imran Khan; Dong Liu; Qiang Fu; Muhammad Azmat; Mingjie Luo; Yuxiang Hu; Yongjia Zhang; Faiz M Abrar (Journal of Earth System Science, 2016)

Isolation and expression analysis of FTZ-F1 encoding gene of black rock fish (Sebastes schlegelii) - Muhammad Shafi; Yanan Wang; Xiaosu Zhou; Liman Ma; Faiz Muhammad; Jie Qi; Quanqi Zhang (Journal of Ocean University of China, 2013)

Nexus between corruption and regional Environmental Kuznets Curve: the case of South Asian countries - Faiz Ur Rehman; Muhammad Nasir; Faiza Kanwal (Environment, Development and Sustainability, 2012)

Synthesis and biological evaluation of some N4-substituted 5-nitroisatin-3-thiosemicarbazones - Humayun Pervez; Nazia Manzoor; Muhammad Yaqub; Faiz-ul-Hassan Nasim; Khalid M. Khan (Medicinal Chemistry Research, 2012)

Synthesis, characterization, and urease inhibition of 5-substituted-8-methyl-2H-pyrido[1,2-a]pyrimidine-2,4(3H)-diones - Abdul Rauf; Sumaira Liaqat; Ashfaq M. Qureshi; Muhammad Yaqub; Aziz U. Rehman; Mahmood U. Hassan; Zahid H. Chohan; Faiz U. H. Nasim; T. Ben Hadda (Medicinal Chemistry Research, 2012)

Coexistence of arbuscular mycorrhizae and dark septate endophytic fungi in an undisturbed and a disturbed site of an arid ecosystem - Muhammad S. Chaudhry; Syed U. Rahman; Muhammad S. Ismaiel; Ghulam Sarwar; Bushra Saeed; Faiz-ul-Hassan Nasim (Symbiosis, 2009)